Golden Hours of Pianoforte Duets, Op. 51, Book 11 - SHUBERT, Franz (Keith Prowse & Co. Ltd)
Di dalam buku ini terdiri dri lagu: Marche Militaire; Melody in F; Spring Song; Largo; Polonaise in A; Habaneraand Toreador's March from 'Carmen'; Hongarian dance, No.3; Dance of the Sugar Plum Fairy; Walte in D Flat; Rigoletto (Quartett); The Mill; The Blue Danube.